Ақпараттық-коммуникативтік технологияларды сабақта пайдаланудың тиімділігі - Күмісбекова, Ж. Н. (My University, 2016)
&he advantages of usage some information- communicative technologies in classes have got the effective influence on development of students intellectual thinking using different technologies, also they have got an influence on development of some art abilities, on seeing some received information, on systematization of knowledge. We have got a century of computerization, the effective usage some ICT on lectures, seminars rises the interest on a lesson, it is rised the searching at students
Keywords: creative; competent; flipchart; video-question